Professional Pre-Higher Education in the European Union Countries: A Review, a Statistical Analysis, and Best Practices - Liesnikova М. V.; Denysiuk, O. Ya. (Statistics of Ukraine, 2025)
The article elaborates on peculiar features of the operation of the professional pre-higher education in EU countries. As the relevance of this study stems from intensive processes of integration of the Ukrainian education system into the European area, it is important to explore how the professional pre-higher education system operates in EU countries, what is its role, forms of obtaining and links with the labor market. The article’s objective is to explore the operation of the professional pre-higher education in EU countries, to make a statistical analysis of its main indicators, and to review best European practices. It was found that the programs of professional pre-higher education were, for the most part, implemented in public colleges and lasted two years. They play the important role in ensuring quick access to job placement, career promotion, and further admission to higher education institutions. Although the average share of trainees by these programs is 8% of the total students, the short-cycle higher education programs have been increasingly popular with EU countries’ residents. This tendency results from the introduction of student-oriented schemes of training, thus opening access to the education for a broad range of people, graduates of vocational training colleges and employed persons alike. The short-cycle higher education programs help implement the concept of lifelong learning, because they are accessible for adults. The most demanded fields of training on line of these programs are “Business, administration, and law”, “Services”, “Engineering, manufacturing, and construction”, “Health protection, and social security”. Subject to analysis were best practices of France, Spain, and Austria, where short-cycle higher education programs covered nearly 20% of the students obtaining higher education. These countries’ experience demonstrates the efficiency of flexible educational trajectories and high estimates for job placement of the graduates, because the short-cycle programs are specifically oriented on the labor market. A potential area for future studies is making a comparative analysis of the operation of short-cycle higher education in Ukraine and EU countries.